Moving the center: Adapting the toolbox of growth model research to emerging capitalist economies - Daniel Mertens; Andreas Nölke; Christian May; Michael Schedelik; Tobias Ten Brink; Alexandre Gomes (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
The growth model perspective has provided positive momentum for Comparative and International Political Economy. This article seeks to move beyond the existing geographical confines of this perspective to elaborate on its potential for enhancing our understanding of the trajectories of different emerging capitalist economies (ECEs), the center of global economic growth during the last decades. Using national accounts data, we calculate the relative contributions of demand components to GDP growth for nine large emerging economies in the period from 2001 to 2016. Departing from the prevalent juxtaposition of consumption-led and export-led growth models, we add an investment-led model within a variegated set of ECE accumulation strategies. Subsequently, we employ case vignettes from Brazil, China, India and Indonesia to highlight ECE specificities in (1) the effects of international interdependencies on growth models, (2) the political underpinnings of growth models through social blocs, and (3) the existence of structural productive heterogeneities leading to regional growth models in very large economies. We conclude that these macro-political and institutional specificities should serve as a point of departure for a more global research agenda on growth models.
Keywords: O11; O19; O43; O57; P52; 330; Comparative capitalism; growth models; emerging capitalist economies; commodity super cycles; social blocs